2018
DOI: 10.1252/jcej.17we277
|View full text |Cite
|
Sign up to set email alerts
|

On the Importance of Modelling Bubble Dynamics for Point-mass Numerical Calculations of Bubble Columns

Abstract: For decades, CFD (computational uid dynamics) has been applied for numerical calculations of the rather complex ow in bubble columns using the two-uid approach (Euler/Euler method) as well as the Euler/Lagrange approach, both based on the point-mass approximation. Numerous di erent models and closures have been proposed and used for describing the uid dynamic forces acting on bubbles, modelling bubble induced turbulence (BIT) and transport of bubbles by turbulence structures (Sommerfeld, 2004). However, the dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 52 publications
(91 reference statements)
0
11
0
Order By: Relevance
“…It was affirmed that the bubble dynamics in the bubble column can be captured by using the adequate SGS‐TDF and SGS‐AMS models in Eulerian‐Eulerian LES modeling, when mimicking the bubble transport in the bubble column. This can imply that the modified SGS‐TDF and SGS‐AMS models may play an equivalent role in indicating the bubble fluctuating motion predicted by using the Euler/Lagrange LES modeling approach but with the stochastic dispersion model 4. Although the case presented in the present study is confined to a circular cylindrical bubble column, it was revealed that the proposed modeling can also be applied to other cases such as a square bubble column.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…It was affirmed that the bubble dynamics in the bubble column can be captured by using the adequate SGS‐TDF and SGS‐AMS models in Eulerian‐Eulerian LES modeling, when mimicking the bubble transport in the bubble column. This can imply that the modified SGS‐TDF and SGS‐AMS models may play an equivalent role in indicating the bubble fluctuating motion predicted by using the Euler/Lagrange LES modeling approach but with the stochastic dispersion model 4. Although the case presented in the present study is confined to a circular cylindrical bubble column, it was revealed that the proposed modeling can also be applied to other cases such as a square bubble column.…”
Section: Discussionmentioning
confidence: 80%
“…Comparison of the time‐averaged bubble axial velocity distribution at z = 325 mm by using three models with experimental and numerical data obtained from Sommerfeld et al. (dots: experimental data 4; dashes: E‐L simulation data 4). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The EL simulation was superior concerning computational time to the EE simulation up to a critical bubble number of 40,000 in the investigated case of a pseudo two dimensional bubble column. Recently, Sommerfeld et al (2018) highlighted the influence of tumpling bubble motion and concluded its relevance to mass transfer, while a direct comparision to mass transfer experiments was not presented. However, in the simulation of bubble columns, many of these models do not describe in detail the motion of individual bubbles, e.g., oscillating or tumbling motion of the bubbles (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Other approaches to the simulation of multiphase flows such as the k-ε model or large-eddy simulation , have also been developed. Some features of multiphase flows such as bubble coalescence and breakup have been challenging to represent accurately using fixed grids .…”
Section: Introductionmentioning
confidence: 99%